Fast, Intelligent and Secure an Embedded Health-care Supervisory System - Neha Shivaji Bidgar (Institute of Advanced Engineering and Science, 2016)
The world of medical supervisory system should remotely monitor various parameters of patients with help of electronics. This work aims at monitoring parameters in fast, intelligent and secure way. The work emphasizes on designing an embedded system which handles critical parameters of patients in hospital/nursing units. The data samples are processed using an ARM based CPU’s and to achieve performance metrics TI RTOS is used and validated. The system generates interrupts based on the priority of each of critical parameters with a threshold in it and enables alarming/warning system. The data is then transferred to IoT layer using a CC3100 TI based SoC for further reference and processing.In this paper, 4 parameters has been monitored for designing system such as measuring Respiratory rate for human breath, MMG signal for muscle movement, Blood pressure rate as well as Temperature. RTOS helps with scheduling as well as with interrupts also helps Wi-Fi module to work with it. Wi-Fi module provides many security options as WEP, WAP, and WAP2.